The scandal of reform : the grand failures of New York's political crusaders and the death of nonpartisanship - Barry, Francis S., 1975- (Book collections on Project MUSE., 2009)
The Scandal of Reform reveals the bonds New York reformers have always shared with the bosses they disdain, the policy failures they still refuse to recognize, and the transition they have made from nonpartisan outsiders to ideological insiders. Francis S. Barry examines the evolution of political reform from the frontlines of New York City's recent reform wars. He offers an insider's account and analysis and he challenges reformers-and members of both parties-to reconsider their faith in reforms that are no longer serving the public interest.